Medical Environment Patient and Bad News - Abdolhassan Kazemi (Kerman University of Medical Sciences, 2008)
Background & Objective: Patients have the right to be informed about their own health condition including bad news and sometimes medical staff has no choice but to give the patients such information that makes them feel bad and is thats when its evaluated as bad news Unfortunately such kind of news is enormously found in medical environment for medical staff patients and their companies The responsibility of telling patients the bad news is one of the hardest tasks in medical career Patients and their companies illogical expectation and inappropriate behavior add to its difficulty while in this situation medical staff is also responsible for calming others Conclusion : The difficult part of telling bad news is due to physicians previous lack of skill even the ones with a proven track record for facing the situation of transferring bad news and further management and consequences which may end in bringing it out of control and causes patients and their companies mistrust in staff or hospital environment This ends in discontinue of future and useful necessary plans This situation causes a faulty circle of unwanted events which are against the medical affairs So a thoughtful bad news transfer to patients and their companies may cause them a relief and makes the control of present and future consequences easier This important factor will be gained by practicing and applying the smart strategy of SPIKES by the professional physician